(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to assess the biodegradation ofplastic bags by Pseudomonas spp. isolated from soil samples collectedfrom landfills in Khartoum State, Sudan. Soil samples were collectedfrom three different locations (A = Khartoum landfill, B = KhartoumNorth landfill, C = Omdurman landfill). The Identification andcharacterizatics of bacteria were done using morphological andbiochemical characterizations. The isolated and standard strains wereadded to the plastic bags in liquid media and then incubated in a rotaryshaker for three weeks to allow time for biodegradation. The initial andfinal dry weights of plastic before and after incubation in the culturemedium were compared and the percentage of degradation wascalculated. The data were subjected to statistical analysis usingcompletely randomized design (CRD). Mean separations were estimatedby Duncan multiple range test (DMRT). This work revealed that thelandfill soil is a good source of microbes capable of degrading plasticmaterials. The isolated strains (Pseudomonas spp.) were found to degradethe plastic bags in the range between 76.4 to 84.8 % within three weeks.Pseudomonas putida was found to degrade the plastic bags up to 85.2 %.The weight loss in plastic bags’ samples is likely due to active enzymesproduced by the bacteria